MBOVPG45_0375 Encodes an IgG-Binding Protein and MBOVPG45_0376 Encodes an IgG-Cleaving Protein in Mycoplasma bovis - Zhao, Haoran; Zhang, Yunke; Wang, Zhanhui; Liu, Mengyao; Wang, Pengpeng; Wu, Wenxue; Peng, Chen (Frontiers in Veterinary Science, 2021)
Mycoplasma bovis is a significant bacterial pathogen which is able to persist in cattle and cause chronic diseases. This phenomenon may relate to M. bovis evading the immune system of the host. Immunoglobulin-binding proteins are widely distributed in a variety of pathogenic bacteria, including some Mycoplasma species. These proteins are considered to help the bacteria evade the immune response of the host. Here we found M. bovis strain PG45 can bind to IgG from several animals. MBOVPG45_0375 encodes a putative membrane protein, has strong amino acid sequence similarity with Immunoglobulin G-binding protein in M. mycoides subsp. capri. Hence, we constructed recombinant MBOVPG45_0375 (r0375) in the Escherichia coli expression system and demonstrated that r0375 can bind to IgG non-immunologically rather than specific binding similar to interaction of antigen and antibody. Moreover, r0375 can bind to the Fab fragment of IgG. Also, the binding of r0375 and IgG inhibits the formation of antigen-antibody union. Furthermore, MBOVPG45_0376 encodes an IgG-cleaving protein of M. bovis strain PG45. Nevertheless, r0375 binding to IgG is required for the cleavage activity of recombinant 0376 (r0376). The activity of r0376 is also affected by incubation time and temperature. In addition, we found both MBOVPG45_0375 and MBOVPG45_0376 are membrane proteins of M. bovis strain PG45. These results about MBOVPG45_0375 as an IgG-binding protein and MBOVPG45_0376 as an IgG-cleaving protein offer a new insight into the interaction between M. bovis and its host.